Information needs of rural farmers in Kedah: A case study of Pusat Internet Desa (PID) - Hussein, Husam Abdulhamed (2016)
Access to accurate, appropriate and reliable information plays a crucial role in improving the rural community’s knowledge and skills. Previous studies have little focus on website that embeds the rural farmers’ information needs. This study aims to determine the rural farmer’s information needs, through the PID of Kedah State, Malaysia. For this purpose, Dervin’s sense making theory was utilized as a guideline. The farmer’s needed information was embedding into a suitable website in two languages, namely local (Malay) and English language, this website would serve the rural farmers in Kedah by managing their farming. A sample size of 200 rural farmers from both genders in Kedah was initially taken to determine their information needs, but the usable data was only 187 respondents were analyzed. Simple random sampling technique was used for the sample selection as well as using of the questionnaire to elicit information from the respondents. SPSS version 20 was used for data analysis, and the data was analyzed in quantitatively approach. The results revealed that the highest information needs were related to the areas of financial facilities, agriculture marketing and pest management. Age, level of education and connectivity to ICT showed significant relationships with their accessibility to information. It is recommended that enough information should be provided in the needed areas and economic empowerment programs should be given serious attention to enhance their access to the needed information. Thirty farmers from different areas of Kedah were chosen to test the usability of the (INRFK) website. General findings revealed that INRFK website satisfied their needs by providing proper information.